Your customer rules ! : - Price, Bill (Jossey-Bass, A Wiley Brand, 2015)
Throughout this practical guidebook, Price and Jaffe share examples of companies who succeed by meeting these seven needs, including Amazon, Apple, IKEA, Nordstrom, USAA, Shoes of Prey, Vente-Privee, and Yamato Transport, as well as those that didn't. Your Customer Rules! offers tailored advice for companies at every stage, from nimble startups to legacy firms with established customer service practices—and everyone in between.With a simple, elegant solution for driving lasting value for customers, Your Customer Rules! is a clear guide for strengthening customer relationships and competing on more than price. It is essential reading for executives at all levels—business owners, marketing managers, and anyone who works directly with customers.